The Role of Culture in Sports Sponsorship: an Update - Sara Keshkar; Ian Lawrence; Mark Dodds; Erin Morris; Tara Mahoney; Kevin Heisey; Francesco Addesa; David Hedlund; Geoff Dickson; Hamid Ghasemi; Abdullah Faruq; Michael Naylor; et al. (The Society of Aging and Physical Activity (SAPA), 2019)
Nowadays sponsorship is an important part of sports events. Sports sponsorship offers more benefits, more variety and also it's a more powerful form of marketing. In general, sponsorship holds a unique position in the marketing mix because it is effective in building brand awareness, provides different marketing platforms and valuable networking and hospitality opportunities. Sponsorship marketing efforts can be influenced by culture. Especially when global sponsorship in sports which refers to sports events in different countries with different cultures, is under consideration. In such situations, sponsorship aspects can be affected by cultural obligations which are discussed in this article